Altruistic Reconstructions: An Examination of Charles Taylor’s Philosophical Anthropology in Man of La Mancha (1972) and Zorba the Greek (1964) - Aghaei, Vahid (Satura, 2020)
Narratives, both real and fictional, are a necessary means to learn about the past (upon which the present is predicated). Moreover, almost all narratives have the capacity of being reinterpreted or re-experienced in a new light. Jacques Derrida uses the term “binary oppositions” for conceptualising experiences within narratives.